Teaching and Learning in Nursing - Pajnkihar, Majda; Vrbnjak, Dominika; Stiglic, Gregor (IntechOpen, 2017)
A significant body of knowledge is the basis for a holistic, caring and scientific evidence-based nursing education in practice for professional development. Quality teaching leads to good learning and both aspects are two of the main issues of quality assurance in nursing education today. To begin with, not all nursing students have the same levels of motivation or learning abilities. It is with cognisance of providing quality care for patients that the role of the nurse educator has to be to enhance nursing students' learning using scientific evidence based teaching. Research around teaching and learning processes is an important part of the delivery of quality education, which in turn impacts on students' learning results and experiences, thereby, ensuring holistic biopsychosocial care to patients. The main aim of teaching and learning in nursing, at all levels, is to enhance the nurses' contribution to assist the individuals, families and communities in promoting and preserving health, well-being and to efficiently respond to illnesses. We hope that this book can be used as a resource to increase the body of knowledge in teaching and learning in nursing, thereby enhancing the role and contribution of health care professionals to clinical practice.